KEPUASAN KONSUMEN GARUDA INDONESIA DITINJAU DARI PELAYANAN, BRAND IMAGE, FASILITAS DAN KEAMANAN (STUDI KASUS DI SURAKARTA) - Febrina Ardiyati; Sri Hartono; Supawi Pawenang (JURNAL ILMIAH EDUNOMIKA, 2020)
The research aims to find out and describe the influence of simultaneously or partial service, brand image, facility and security towards Garuda Indonesia consumer satisfaction in Surakarta. This methodology research using quantitative descriptive research. The population was all Garuda Indonesia consumers in Surakarta are unknown number. The number of samples was determined with the formula Lemeshow and the result 100 respondents. Sampling method using convenience sampling. The questionnaire used for data retrieval. Data analysis technique used was statistic analysis. This test results the service, brand image, facility and security simultaneously and significance effect on Garuda Indonesia consumer satisfaction in Surakarta. Service influential positive and significance effect against the Garuda Indonesia consumer satisfaction in Surakarta. Brand image influential positive and significance effect against the Garuda Indonesia consumer satisfaction in Surakarta. Facility influential positive and significance effect against the Garuda Indonesia consumer satisfaction in Surakarta. Security influential positive and significance effect against the Garuda Indonesia consumer satisfaction in Surakarta. Keywords : Consumer Satisfaction, Service, Brand Image, Facility, Security